Creep behaviour of WC-12 wt% Co hardmetals with different WC grain sizes tested in uniaxial tensile and compression step-loading tests at 700 °C and 800 °C. (November 2021) - Maier, Kathrin; Klünsner, Thomas; Krobath, Martin; Pichler, Philip; Marsoner, Stefan; Ecker, Werner; Czettl, Christoph; Schäfer, Jonathan; Ebner, Reinhold
Abstract: At elevated temperatures, the material behaviour of WC-Co hardmetals shows differences under similar loading conditions depending on WC grain size and Co-content. Variations in the chemical composition and microstructure in hardmetals cause different material properties such as strength or creep resistance. In the current work, the influence of WC grain size on creep mechanism and creep resistance was investigated for WC-12 wt% Co hardmetals with 0.4 μm, 0.7 μm and 2.0 μm average WC grain size. Specimens were tested in uniaxial tensile and compression step-loading creep tests at 700 °C and 800 °C under vacuum conditions. Time-dependent creep behaviour with steady-state secondary creep was observed for all hardmetal grades investigated, with specimens creeping faster under tensile than under compressive loading. At 700 °C, the medium-grained hardmetal grade exhibited the highest minimal creep rates ε ̇ min compared to the submicron and ultrafine-grained grades. In contrast, the ultrafine-grained hardmetal grade showed higher ε ̇ min at low stresses and 800 °C, because of the high amount of grain boundary area per unit volume, which is advantageous for vacancy diffusion at grain boundaries. Therefore, the ε ̇ min of the medium-grained hardmetal grade was less affected by temperature than that of the finer-grained grade. Also two stress exponent n -ranges were observed at 700 °C and 800 °C: At low stress levels, n was in the range of about 1. Above a critical stress level, n reached values between about 4 and 6. Beside the influence of the WC grain size on the creep mechanism and creep resistance, damage evolution with increasing stress levels was analysed for the ultrafine-grained grade at 800 °C. The microstructures of three compression step-loading creep tested specimens were examined after maximum stress levels of −350 MPa, −950 MPa and −1350 MPa. Microstructural investigations performed via scanning electron microscopy showed that more and larger cavities had formed at WC/WC interfaces and WC/Co phase boundaries in the specimen tested up to −1350 MPa compared to the ones tested up to −350 MPa and −950 MPa. Highlights: Compression & tensile step-loading creep behaviour for WC-12wt.% Co hardmetals (WC grain 0.4 to 2.0 µm) at 700 °C & 800 °C. Flexible test setup, as specimens can be loaded at low or high temperatures up to high operating loads. Medium & submicron grades' creep rate is less affected by increasing temperature & vacancy diffusion than ultrafine grade. Two stress exponents n at 700 °C & 800 °C: low stress levels n ≈ 1, & above a critical stress level, n is between ≈ 4 & 6. Microstructure study of the ultrafine grade shows an increase in the number of microdefects & their size at high stress levels.